A Nationwide Survey of Cytomegalovirus Prevention Strategies in Kidney Transplant Recipients in a Resource-Limited Setting. (8th July 2019) - Bruminhent, Jackrapong; Bushyakanist, Asalaysa; Kantachuvesiri, Surasak; Kiertiburanakul, Sasisopin
Abstract: Objective: Strategies to prevent cytomegalovirus (CMV) infection in resource-limited settings have been under-explored. We investigated CMV prevention strategies utilized among transplant centers in Thailand. Method: A questionnaire on CMV prevention strategies for kidney transplant (KT) recipients was developed using a web-based electronic survey website (www.surveymonkey.com ). The survey was delivered to 31 transplant centers in Thailand. One infectious disease physician (ID) and 1 nephrologist (NP) from each center were included. Results: There were 43 respondents from 26 of the 31 transplant centers (84%), including 26 (60%) IDs and 17 (40%) NPs. Forty-one 95% (41/43) physicians agreed on the necessity of CMV prevention. Of these, 77% (33/43) physicians implemented prevention strategies for their patients. Interventions included preemptive approaches (48%), prophylaxis (45%), hybrid approaches; surveillance after prophylaxis (3%), and CMV-specific immunity-guided approaches (3%). For CMV-seropositive KT recipients, use of preemptive approaches (84%) exceeded prophylaxis (12%). However, 81% of the former preferred targeted prophylaxis in patients receiving antithymocyte globulin therapy. Sixty-five percent and 93% of physicians started preemptive therapy when plasma CMV DNA loads reached 2000 and 3000 copies/mL (1820 and 2730 IU/mL), respectively. A significantly greater percentage of NPs initiated preemptive therapy at a plasma CMV DNA load of 1820 IU/mL compared with IDs (88% vs 50%; P = .02). The most common barrier to prevention strategy implementation was financial inaccessibility of oral valganciclovir (67%) and quantitative CMV DNA testing (12%). Conclusions: Most physicians agreed on a need for preemptive approaches, although prophylaxis was targeted in those receiving intense immunosuppression. The financial implication is the main barrier for CMV prevention in Thailand.